Potensi Bakteri Zoogloea Sp sebagai Bakteri Pembentuk Bioflok pada Sistem Pertambakan - Muhammad, Junda (bionature, 2011)
The objective of this study was to know the potency of  bacteria zoogloea sp as indigenous bacteria  from shrimp pond farming in colonizing particles. Study of  particle-colonizing capacity of Zoogloea sp by using artificial-sphare agar and transparant exopolimeric particles (TEP) produced by fitoplankton, Thalassiosira weisfloggii. The results showed that Zoogloea sp were able to coloninize both artificial-agar spheres and TEP produced by T. weisfloggii.The mean number of  Zoogloea sp colonizing artificial-agar sphares increasing with incubation time was 2,70 x 104 cells/agar sphere. In the test of TEP-colonizing bacteria showed that Zoogloea sp was able to colonize  the TEP i.e. 2.5 x 108 cells/mL. after 4 days incubation. It can be concluded that Zoogloea sp isolated from shrimp pond farming has a high potential in colonizing particles.